An Analysis of the Interpretation of Dream in Demi Ucok Movie - Sihombing, Lambok Hermanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Dreams are constructed narratives and visuals by our imaginations. This article discusses an Indonesian movie about Batak culture, especially their unique tradition when it comes to marriage. In this scientific article, the author aims to analyze how the characters in Demi Ucok movie interpret their dreams, especially in finding out a companion such as a life partner. In order to help the author doing this analysis, Mise En Scene approach from Manon de Reeper and Theory of Interpretation of Dream from Sigmund Freud are used for this study. The result of this study indicates that this film represents Batak people’s dream and wishes of seeing their children getting married with Batak people because Batak culture is quite strict about marriage. In Batak tradition, getting married to the same tribe is their life philosophy; Hagabeon, Hamoroan, and Hasangapon, and every Bataknese are trying to get married to the same tribe along with a certain cultural practice